2019
DOI: 10.1016/j.asieco.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of media campaigns on tax filing: quasi-experimental evidence from Pakistan

Abstract: This paper examines the effect of mass media campaigns on income tax filing using survey data from Pakistan. We use information collected about a pro-tax filing communication campaign shortly after the 2013-14 tax filing deadline by Pakistan's Federal Board of Revenue. We use an inverse probability-weighted regression adjustment estimator to construct comparable treatment and control groups in terms of media exposure and control for predictors of income tax filing. We find that respondents' likelihood of incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…(Victor, 2015). Furthermore, We find that tax filing income has increased in response to exposure to newspaper ads that provided information on tax eligibility but not in response to those that reported the tax filing deadline or the financial penalties of not filling (Koumpias, 2019). On the other hand, with tax administration reforms, taxpayers are expected to be able to obtain better tax services so that tax problems will be resolved faster with more secure legal certainty.…”
Section: Preliminarymentioning
confidence: 84%
“…(Victor, 2015). Furthermore, We find that tax filing income has increased in response to exposure to newspaper ads that provided information on tax eligibility but not in response to those that reported the tax filing deadline or the financial penalties of not filling (Koumpias, 2019). On the other hand, with tax administration reforms, taxpayers are expected to be able to obtain better tax services so that tax problems will be resolved faster with more secure legal certainty.…”
Section: Preliminarymentioning
confidence: 84%
“…A prominent shortcoming is that individuals' answers to the question may not correlate with actual tax behavior; some individuals may want to make up for past behavior by asserting high tax morale in survey responses. Several papers (Cummings et al, 2009;Halla, 2012;Koumpias and Martinez-Vazquez, 2019) have shown evidence of a causal link between tax morale and a some measure of tax compliance. Other issues contemplated in the literature, such as the problems derived from using a single question to 10 Typically, tax morale is coded into an ordered variable in four different categories.…”
Section: Model Selectionmentioning
confidence: 99%
“…Advertising tax itself is a tool used as a bridge between producers and consumers to introduce products produced by companies or other functions with the same purpose (Konfino et al, 2015). Because the billboard tax is located at strategic points and is widely accessible by the public, billboards are one of the most appropriate media to promote products to the public (Koumpias & Martinez-Vazquez, 2019). Besides billboards, they can be in the form of boards, advertising advertisements, such as newspapers, magazines, etc., and electronic media such as television, radio, and social media (Cyan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%